1992
DOI: 10.1002/j.2161-0045.1992.tb00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Role Conflict and Career Advancement Among African American Women in Nontraditional Professions

Abstract: To investigate differences in the career experiences of Black women in traditional and nontraditional professions, a sample of Black professional women in traditional (e.g., social work, teaching, counseling) and nontraditional (e.g., law, medicine, engineering) professions were mailed a questionnaire asking about career experiences, family life, and other personal characteristics. Marriage was reported to be more of a career barrier for nontraditionals than traditionals. Nontraditionals also reported more car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Research regarding career barriers in minority groups shows that ethnic discrimination is the only barrier specific to these groups that occurs independently of the life cycle phase or the ethnic minority group (Burlew & Johnson, 1992;Gomez, Fassinger, Prosser, Cooke, Mejia & Luna, 2001;Jackson & Nutini, 2002;Juntunen, Barraclough, Broneck, Seibel, Winrow, & Morin, 2001;Luzzo, 1993;Luzzo & McWhirter, 2001). Other kinds of barriers, non-specific to these populations, are related to each of the ethnic minority groups illustrating particularities of their career development.…”
Section: Abstract Career Barriers á Gender Differences á Minoritiesmentioning
confidence: 92%
“…Research regarding career barriers in minority groups shows that ethnic discrimination is the only barrier specific to these groups that occurs independently of the life cycle phase or the ethnic minority group (Burlew & Johnson, 1992;Gomez, Fassinger, Prosser, Cooke, Mejia & Luna, 2001;Jackson & Nutini, 2002;Juntunen, Barraclough, Broneck, Seibel, Winrow, & Morin, 2001;Luzzo, 1993;Luzzo & McWhirter, 2001). Other kinds of barriers, non-specific to these populations, are related to each of the ethnic minority groups illustrating particularities of their career development.…”
Section: Abstract Career Barriers á Gender Differences á Minoritiesmentioning
confidence: 92%
“…Furthermore, women in STEM careers are more likely than women in other professions to report that family responsibilities interfered with their work (Burlew & Johnson, 1992). Nauta and colleagues (1998) found that perceived role conflict was a predictor of and potential obstruction to women's leadership aspirations within STEM professions.…”
Section: Stereotypes and Normsmentioning
confidence: 99%
“…Other researchers have noted that the perceived demands of STEM occupations are viewed as especially burdensome when young women anticipate or have family responsibilities (Seymour & Hewitt, 1997;Ware & Lee, 1988). Young women may then reject STEM goals because they do not perceive ways to combine their career and family roles (Arnold, 1993;Betz, 1994;Burlew & Johnson, 1992;Lips, 1992;Livingston & Burley, 1991;Nauta et al, 1998).…”
Section: Perceptions Of Stem Careersmentioning
confidence: 99%
“…Indeed, individuals who belong to stigmatized groups are more likely than are their nonstigmatized counterparts to report that they have experienced discrimination in the past and expect to be discriminated against in the future (Major, McCoy, Kaiser, & Quinton, 2003). Furthermore, they are more likely to cite discrimination as a barrier to their success (e.g., Burlew & Johnson, 1992; Foley & Kidder, 2002; McWhirter, 1997). Thus, the expectation of encountering prejudice is apt to lead to lower expectations of success.…”
Section: Expectancy/value Theories Of Motivationmentioning
confidence: 99%